Increase in Skin Temperature After Spinal Anesthesia in Infants. Issue 6 (1st November 2006) - Jetzek-Zader, Martin; Hermanns, Henning; Freynhagen, Rainer; Lipfert, Peter; Stevens, Markus F.
Abstract : Background and Objectives: The relatively stable hemodynamics during spinal anesthesia in infants have been attributed to a less active sympathetic nervous system in comparison with adults. Thus, the authors evaluated sympathetic block primarily by measurement of skin temperature and secondarily by determination of noninvasive blood pressure as an indirect sign of sympatholysis. Methods: In 15 infants (postconceptual age: 45.0 ± 4.8 weeks; weight: 4.0 ± 1.2 kg) scheduled for repair of inguinal hernia under spinal anesthesia, skin temperature at the T4 level and at the plantar foot was measured before and after spinal anesthesia. Spinal anesthesia was induced at the L4/L5 interspace with 0.5% hyperbaric bupivacaine 1 mg/kg with 10 μg/kg adrenaline added. Results: Temperature at the plantar foot after spinal anesthesia rose significantly from 33.0°C ± 1.3°C to 34.7°C ± 1.4°C within 10 minutes and to 35.6°C ± 0.9°C after 20 minutes ( P < .0001), whereas the temperature at the thorax remained constant at 35°C to 36°C. Systolic and diastolic blood pressure decreased by 15.9 ± 11.4 mm Hg and 9.0 ± 9.2 mm Hg, respectively ( P < .01), but remained within normal range in all cases. Conclusions: The authors found a significant increase in skin temperature of the feet within 10 minutes as a sign of sympatholysis, whereas trunk temperature remained constant. Blood pressure decreased but remained within the normal range, despite the observed sympatholysis.